2017
DOI: 10.1371/journal.pone.0188223
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and potential activity of methanotrophs in high methane-emitting permafrost thaw ponds

Abstract: Lakes and ponds derived from thawing permafrost are strong emitters of carbon dioxide and methane to the atmosphere, but little is known about the methane oxidation processes in these waters. Here we investigated the distribution and potential activity of aerobic methanotrophic bacteria in thaw ponds in two types of eroding permafrost landscapes in subarctic Québec: peatlands and mineral soils. We hypothesized that methanotrophic community composition and potential activity differ regionally as a function of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 108 publications
(124 reference statements)
6
44
0
Order By: Relevance
“…However, we only found a significant and unimodal relationship between type II methanotrophs relative abundance and temperature, perhaps due to fact that most of the samples were taken during the summer and the temperature gradient was relatively modest. Oxygen is also reported as a highly influential variable in the literature (Crevecoeur et al, ; Martinez‐cruz et al, ; Oswald et al, ; Reim, Lüke, Krause, Pratscher, & Frenzel, ) and in our data set we observed declining trend of both types as a function of oxygen concentration, in spite of the relatively narrow range oxygen gradient present in our data, since samples were all taken in the well mixed surface layers of rivers and lakes. Overall, variation in pH and p CH 4 seems to be leading to different responses of type I and type II in our data set, suggesting that those variables are amongst the ones that could be responsible for the niche partition between type I and type II methanotrophs at large scales.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…However, we only found a significant and unimodal relationship between type II methanotrophs relative abundance and temperature, perhaps due to fact that most of the samples were taken during the summer and the temperature gradient was relatively modest. Oxygen is also reported as a highly influential variable in the literature (Crevecoeur et al, ; Martinez‐cruz et al, ; Oswald et al, ; Reim, Lüke, Krause, Pratscher, & Frenzel, ) and in our data set we observed declining trend of both types as a function of oxygen concentration, in spite of the relatively narrow range oxygen gradient present in our data, since samples were all taken in the well mixed surface layers of rivers and lakes. Overall, variation in pH and p CH 4 seems to be leading to different responses of type I and type II in our data set, suggesting that those variables are amongst the ones that could be responsible for the niche partition between type I and type II methanotrophs at large scales.…”
Section: Discussionsupporting
confidence: 52%
“…DOC also emerged as one of the strongest predictors of methanotrophic community composition, especially when soils and soil waters were considered, supporting the strong link between the dynamics of methane oxidation and DOC concentration observed across boreal lakes (Thottathil et al, ). This link, which has been previously hypothesized (Crevecoeur et al, ), has only been explained by indirect causes so far, for example via the inhibitory effect of light on methanotrophy (Murase & Sugimoto, ) with higher DOC environments providing protection against light inhibition (Thottathil et al, ). Alternatively, DOC may also favour methanogenesis by influencing the resources available to methanotrophs and also by promoting bottom water anoxia in lakes (Thottathil et al, ).…”
Section: Discussionmentioning
confidence: 90%
“…This latter process in known to occur in anoxic as well as oxygenated environments (Oswald et al, ), including in subarctic lakes (Martinez‐Cruz et al, ). Consistent with these observations, molecular microbiological studies have shown the presence of methane oxidation potential (specifically RNA transcripts of the gene coding for the pmoA subunit of the methane oxidizing enzyme) in both aerobic and anaerobic strata in these lakes (Crevecoeur et al, ). The results presented here show that methane can accumulate for prolonged periods of time, either under the ice during winter or in deep hypolimnetic waters during summer stratification.…”
Section: Discussionmentioning
confidence: 64%
“…Although previous work has found O 2 ‐limited CH 4 oxidation in surface waters of GSL in the summer (one out of five O 2 ‐limited lakes from 25 total study lakes in Martinez‐Cruz et al, ), this study asserts that evidence of 13 CH 4 enrichment in both surface and deep waters of GSL is enough to validate the rough estimate provided by the open‐system model. Additionally, recent studies have also found evidence for higher‐than‐expected methanotrophy at low oxygen concentrations in permafrost ponds (Crevecoeur et al, ) and alpine lakes (Blees et al, ), suggesting that CH 4 consumption may be primarily influenced by the concentration of CH 4 substrate and thus consistent with first‐order kinetics. Since we did not measure dissolved O 2 in this study, we acknowledge these assumptions as sources of error in our estimates of seasonal CH 4 consumption.…”
Section: Methodsmentioning
confidence: 77%